Implementation of green marketing, quality brand consumer behavior, and impact purchase decisions for precious metal products - Karim, Abdul; Ahmad, Amrullah; Remmang, Hasanuddin; Chahyono (International Journal of Management and Sustainability, 2025)
This study aims to analyze the effect of green marketing implementation, brand quality, and consumer behavior on purchasing decisions for precious metal products. The main focus is on how the environmental aspect, brand image, and consumer preferences and behavior affect the decision-making process. A quantitative approach was used with a survey method through a structured questionnaire distributed to precious metal consumers. Data were analyzed using the Structural Equation Modeling (SEM) method to test the relationship between variables with the target population consisting of consumers who actively purchase precious metal products. Green marketing has a significant positive impact on purchasing decisions because consumers are beginning to realize the importance of products that support environmental sustainability. Brand quality plays an important role in increasing consumer trust in precious metal products reflected in loyalty and positive recommendations. Consumer behavior includes environmental awareness, investment preferences, and attitudes toward risk significantly influencing purchasing decisions. The combination of green marketing strategies and strengthening brand quality increases the attractiveness of precious metal products in the market. Success in marketing precious metal products depends on the implementation of an effective green marketing strategy accompanied by improving brand quality relevant to modern consumers’ needs. Precious metal producers need to strengthen sustainability-based marketing strategies by highlighting the ecological advantages of their products. Market education on the importance of choosing environmentally friendly products can increase consumer awareness and loyalty to precious metal products. Collaboration with environmental certification bodies provides additional credibility to green marketing claims.